Deubiquitinase ubiquitin-specific protease 3 (USP3) inhibits HIV-1 replication via promoting APOBEC3G (A3G) expression in both enzyme activity-dependent and -independent manners. Issue 22 (20th November 2022) - Zhao, Simin; Zheng, Baisong; Wang, Liuli; Cui, Wenzhe; Jiang, Chunlai; Li, Zhuo; Gao, Wenying; Zhang, Wenyan
Abstract: Background: Ubiquitination plays an essential role in many biological processes, including viral infection, and can be reversed by deubiquitinating enzymes (DUBs). Although some studies discovered that DUBs inhibit or enhance viral infection by various mechanisms, there is lack of information on the role of DUBs in virus regulation, which needs to be further investigated. Methods: Immunoblotting, real-time polymerase chain reaction, in vivo / in vitro deubiquitination, protein immunoprecipitation, immunofluorescence, and co-localization biological techniques were employed to examine the effect of ubiquitin-specific protease 3 (USP3) on APOBEC3G (A3G) stability and human immunodeficiency virus (HIV) replication. To analyse the relationship between USP3 and HIV disease progression, we recruited 20 HIV-infected patients to detect the levels of USP3 and A3G in peripheral blood and analysed their correlation with CD4 + T-cell counts. Correlation was estimated by Pearson correlation coefficients (for parametric data). Results: The results demonstrated that USP3 specifically inhibits HIV-1 replication in an A3G-dependent manner. Further investigation found that USP3 stabilized 90% to 95% of A3G expression by deubiquitinating Vif-mediated polyubiquitination and blocking its degradation in an enzyme-dependent manner. It also enhances the A3G messenger RNA (mRNA) level by binding to A3G mRNA and stabilizing it in an enzyme-independent manner. Moreover, USP3 expression was positively correlated with A3G expression ( r  = 0.5110) and CD4 + T-cell counts ( r  = 0.5083) in HIV-1-infected patients. Conclusions: USP3 restricts HIV-1 viral infections by increasing the expression of the antiviral factor A3G. Therefore, USP3 may be an important target for drug development and serve as a novel therapeutic strategy against viral infections.